If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2g + 4 = 4g + -8 Reorder the terms: 4 + 2g = 4g + -8 Reorder the terms: 4 + 2g = -8 + 4g Solving 4 + 2g = -8 + 4g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-4g' to each side of the equation. 4 + 2g + -4g = -8 + 4g + -4g Combine like terms: 2g + -4g = -2g 4 + -2g = -8 + 4g + -4g Combine like terms: 4g + -4g = 0 4 + -2g = -8 + 0 4 + -2g = -8 Add '-4' to each side of the equation. 4 + -4 + -2g = -8 + -4 Combine like terms: 4 + -4 = 0 0 + -2g = -8 + -4 -2g = -8 + -4 Combine like terms: -8 + -4 = -12 -2g = -12 Divide each side by '-2'. g = 6 Simplifying g = 6
| 2(x+1)=4x-10 | | 3=h-9 | | 8-y=(7+y)3 | | 8-y=(7+y) | | x+.07x=20 | | 12-4(5a-1)=2(3a+6)-4a | | (61-10x)=(5x+7)*3 | | 61-10x=(5x+7)3 | | -3(2x+1)-20=8x+5 | | 7(3x-8)-20x=7 | | -2+8x+5=2x-21 | | 6(5x+7)=30x+42 | | 4(1-c)-1=2(3-5c) | | -7x=11x-16 | | -4(5-2a)+3(a-4)=6(2-a)-5a | | 0.8888x=-64 | | 0.1=10n | | 0.5(2y-1)-(0.5-0.2y)+1=0 | | 6+(2-4x)+5=3(1-3x) | | 3x-5(2-x)=54 | | -15+z=11 | | 20+x-4=-1+16 | | 20+x-4=2x-8 | | x(.08)+X=240 | | xx=x | | 8x-5x-3x-2=13 | | 8=2x-4+6 | | 2ax^2-ax^2= | | (2)x-x-3=-2 | | K+28=26 | | 33=9-2h | | 2c+3d+4c-d= |